ANALISIS POSTUR KERJA DAN KARAKTERISTIK PEKERJA TERHADAP KELUHAN MSDs KARYAWAN PT VWX - PRASENA, RIZAL WAHYU; Zetli, Sri (LPPM Universitas Putera Batam, 2021)
There are still many work processes that are done manually which require someone to have more abilities in bones and muscles. However, a person's ability is also limited, so that when doing manual work, muscle complaints often occur, namely Musculoskeletal Disorders (MSDs). Activities carried out at PT VWX are still manual, especially in the drum reception and spare part material storage, so there are many complaints in this activity. This study aims to determine the subjective complaints of MSDs, the level of ergonomics risk and the relationship between work posture, age, body mass index, exercise habits and smoking habits on MSDs complaints. The instruments used are NBM questionnaire, work posture pictures and worker characteristics questionnaire. The NBM questionnaire showed that subjective complaints were mostly felt on the back with a score of 35 (87.5%). The method used is the REBA method with the calculation results having a high level of risk, namely in the drum reception section an average score of 9 and in the spare part material storage section an average score of 8.3. Based on the results of research tests related to MSDs complaints are work posture, age and body mass index, with a significance value of <0.05, while those that are not related to MSDs complaints are exercise habits and smoking habits, with a significance value of > 0.05.